Sistem Pendukung Keputusan Menggunakan Metode Fuzzy Simple Additive Weighting (F-SAW) Untuk Menentukan Status Gizi Buruk Balita Pada Puskesmas Tetaf Kecamatan Kuatnana Kabupaten Timor Tengah Selatan - Kornelis Letelay; Bertha S Djahi; Marni Nokas (J-Icon : Jurnal Komputer dan Informatika, 2021)
In NTT, the number of malnutrition cases among children under five have increased annually. TTS regency is in the top three in terms of the number of cases of malnutrition with 442 cases of under-five in 2016. In Tetaf Health Center, Kuatnana Disctrict, the status of malnutrition has been determined manually which results in the inappropriate service. Therefore, a system is needed aiding in providing right recomendation which leads to appropriate service. In this paper, a decision support systems (DSS) approach in determining malnutrition status in toddlers has been implemented by using Fuzzy Simple Additive Weighting (F-SAW) with four criteria, namely, age, a comparison of weight (kg) to age, a comparison of height (cm) to age, and gender. This study uses accuracy testing. Accuracy testing obtained an accuracy rate of 100% from 50 data, with 8 under-nutrition toddlers, 7 malnourished toddlers, and 35 toddlers with good nutrition.